BS23 mRNA expression profiling of dual specificity phosphatases (DUSPS) in the hypertensive heart. (4th June 2021) - Haines, Zoe; Cull, Josh; Baldwin, Samuel; Whitley, Guy; Clerk, Angela; Meijles, Daniel
Abstract : Introduction: DUSPs dephosphorylate Ser/Thr and Tyr residues, most notably in the mitogen-activated protein kinases (MAPKs) that are activated by dual phosphorylation in a T-X-Y motif. Whereas some DUSPs preferentially dephosphorylate nuclear MAPKs (DUSP1/2/4/5), others dephosphorylate cytoplasmic MAPKs, including growth-promoting ERK1/2 (DUSP6/7/9) and stress-responsive p38-MAPKs or JNKs (DUSP8/10/16). MAPKs regulate cell growth/survival/death and are implicated in hypertensive heart disease. DUSPs may fine-tune these pathways and influence cardiac remodelling. Here, we assessed expression profiles of cardiac DUSP mRNAs in human heart failure and hypertensive rodents. Methods: Cardiac DUSP (DUSPs 1, 2, 4, 5, 6, 7, 8, 9, 10 and 16) mRNA expression was assessed in an archive of human left ventricular tissue from control (n=12) and non-ischemic heart failure (n=12) individuals. Rodent hypertension models were also studied: spontaneously hypertensive rats (SHRs; 11-13 weeks, n=8) were compared to age-matched WKY controls (n=8), and C57BL/6J male mice (10 wks) were infused with vehicle (acidified-PBS, n=16) or 0.8 mg/kg/d angiotensin II (AngII) for 24h (n=11) or 7d (n=12) using osmotic minipumps. In all studies, cardiac DUSP mRNA expression was assessed by qPCR relative to GAPDH. Statistical tests used a 1-way ANOVA with Holm-Sidak post-test (mouse studies) and unpaired t-tests (human and rat studies). Results: All DUSPs were detected in human hearts except DUSP5; DUSP7 was significantly suppressed (0.53±0.045-fold, p=0.0065) in failing hearts. All DUSPs were detected in rat or mouse hearts. With chronic hypertension in SHRs, Dusp2 (1.39±0.10-fold, p=0.0090), Dusp4 (1.90±0.17-fold, p=0.0004), Dusp6 (1.31±0.15-fold, p=0.0190), Dusp7 (1.48±0.05-fold, p<0.0001), Dusp8 (2.01±0.15-fold, p=0.0024) and Dusp16 (1.22±0.05-fold, p=0.0295) were all upregulated relative to WKY controls, whilst Dusp9 was decreased (0.33±0.08-fold, p=0.0232). In contrast, in the acute model of murine hypertension with AngII-treatment, there were significant increases in Dusp8 (1.48±0.12 fold, p=0.0003), Dusp10 (1.54±0.08-fold, p<0.0001) and Dusp16 (1.37±0.06-fold, p=0.0306) abundance at 24h, whilst only Dusp6 (1.47±0.11-fold, p=0.0013) was elevated at 7 days relative to vehicle controls. Conclusion: DUSPs are expressed in human and rodent hearts. With acute adaptation to hypertension, changes in DUSP profiles potentially modulate activities of stress-responsive MAPKs. However, in established hypertension and human heart failure, changes in DUSP profiles potentially modulate activities of cytoplasmic ERKs. Thus, DUSPs are likely to contribute to development of hypertensive heart disease. Conflict of Interest: None